Determination of Women's Electability in The 2024-2029 Jambi Provincial Legislative Council Elections - Mariatul Qibtiyah; Beriansyah, Alva; Elsi, Sutri Destemi (Kemudi, 2026)
Women's representation in Indonesian politics is an important indicator of the quality of democracy and gender equality. Although an affirmative policy of 30% female participation in legislative candidate lists has been implemented, the level of women's electability remains low. This article examines the determinants of women's electability in the 2024–2029 Jambi Provincial Legislative Council (DPRD) elections using Casey's theory of political capital, which includes institutional, social, cultural, economic, and symbolic capital. This study uses a qualitative approach with a descriptive-analytical method to understand the factors that influence women's political success at the local level. The results show that of the 732 legislative candidates for the Jambi Provincial DPRD, 247 or 33.74% were women, but only seven (12.72%) were successfully elected. This phenomenon reveals a gap between symbolic representation and substantive representation. An analysis of political modalities shows that women who were successfully elected generally possessed a strong combination of capital—institutional support from parties (institutional capital), extensive social networks (social capital), credibility and education (cultural capital), financial capabilities s (economic capital), and moral legitimacy and public reputation (symbolic capital). These findings confirm that women's political success is not only determined by affirmative regulations, but also by the ability of female actors to strategically manage and convert various forms of political capital. This article provides empirical and theoretical contributions to strengthening a more gender-responsive inclusive democracy.